What halts democratic erosion? The changing role of accountability. Issue 5 (4th July 2021) - Laebens, Melis G.; Lührmann, Anna
ABSTRACT: Worldwide, democratic erosion is on the rise, with incumbents slowly undermining the pillars of democratic competition such as political freedoms, clean elections, and a free press. While such gradual erosion frequently culminates in democratic breakdown, this is not always the case. How can accountability mechanisms contribute to halting democratic erosion before breakdown, even if they could not prevent the onset of erosion? To study this question, we use the V-Dem Electoral Democracy Index to systematically identify three recent cases – Benin (2007–2012), Ecuador (2008–2010), and South Korea (2008–2016) – where substantial democratic erosion happened but democracy did not break down. Studying these cases in depth we find that accountability mechanism – parliamentary and judicial oversight (horizontal accountability), pressures from civil society and the media (diagonal accountability), or electoral competition between parties and within parties (vertical accountability) – played a part in halting democratic erosion in all of them. They effectively halted erosion when institutional constraints – such as presidential term limits or judicial independence – and contextual factors – in particular economic downturns and public outrage about corruption scandals – worked together to create simultaneous pressures on the incumbents from civil society and from vertical or horizontal accountability actors.